2018
DOI: 10.4103/ijpvm.ijpvm_199_17
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects of Rosa damascena extract on patients with neurocognitive disorder and depression: A clinical trial study

Abstract: Background:Dementia as a major cognitive neurological disorder is defined as impairment in one or more cognitive territories compared with the former level of performance. This disorder disrupts patient's independence, and the patient would need others aid in order of doing daily and complex activities. The aim of this study was to evaluate the efficacy of Rosa damascena extract in the improvement of cognitive function in patients with dementia.Methods:This study is a randomized double-blind, placebo-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Rosa damascena extract has been reported to significantly reduce dementia patients' cognitive impairment [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosa damascena extract has been reported to significantly reduce dementia patients' cognitive impairment [8].…”
Section: Discussionmentioning
confidence: 99%
“…Aromatherapy is usually administered through inhalation because essential oils vaporize easily [1]. Many studies have shown the positive effects of pure essential oils on attention span [2], recall speed and quality [3], memory performance [4,5], short-term memory [6], image memory [7] in healthy individuals and on memory and moods in the cognitive disorders of dementia [8]. These effects occur due to the connections of the tractus olfactorius to the limbic system and the hypothalamus [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these effects may be due to the inhibition of serotonine reuptake. 32 The Anti-anxiety and anti-depressive effects of R. damascena were shown in Table 1.…”
Section: Effect On Depression and Anxietymentioning
confidence: 99%
“…Furthermore, oral administration of Jollab (an extract of RDM) significantly reduced depression amongst patients suffering from functional dyspepsia (Pasalar et al, 2015). Other RCTs also reported the effects of RDM on anxiety or depression induced by labor (Hamdamian et al, 2018;Kheirkhah, Setayesh Valipour, Nisani, & Haghani, 2014), HD (Barati, Nasiri, Akbari, & Sharifzadeh, 2016), burn dressing (Daneshpajooh, Najafi Ghezeljeh, & Haghani, 2019;Sadeghi, Azizi, Asgari, & Mohammadi, 2020), surgery (Amini & Alizadeh, 2018;Bastani, Samady Kia, & Haghani, 2020;Najafi, Sajjadi, Nasirzadeh, & Jeddi, 2020;Noorian, Madadkar Dehkordi, Doosti Irani, & Azari, 2020;Seyyed-Rasooli, Amiri, Zamanzadeh, Peron, & Aghakeshizadeh, 2014), menstruation (Jamilian, Jamilian, & Mirzaie, 2013), job (Gholami, Teymouri, Farsi, & Rajai, 2019), hospitalization (Hashemi Siyavoshani, Fallahi Arezodar, Pishgooei, & Jadid Milani, 2020;Jodaki et al, 2021), and dementia (Esfandiary et al, 2018).…”
Section: Introductionmentioning
confidence: 99%